Eculizumab Induces Sustained Remission in a Patient With Refractory Primary Catastrophic Antiphospholipid Syndrome. Issue 6 (September 2015) - Zikos, Thomas A.; Sokolove, Jeremy; Ahuja, Neera; Berube, Caroline
Abstract : Abstract: Catastrophic antiphospholipid syndrome (CAPS) is fatal in approximately 44% of patients in whom the diagnosis is made, thus demonstrating the inadequacy of current medical therapy. In this report, we discuss a 47-year-old man with a known history of primary antiphospholipid syndrome, who presented with CAPS after undergoing cholecystectomy and a treatment-refractory early relapse after development of colitis. Given the potential therapeutic efficacy of complement inhibition in antiphospholipid syndrome, the patient was administered eculizumab, a terminal complement inhibitor. Progressive clinical improvement and laboratory improvement were observed upon initiation of eculizumab. He has remained in remission for over 16 months of follow-up while on eculizumab. In conclusion, this case represents successful use of eculizumab for the treatment of primary CAPS.